Development of a New Epitope Tag Recognized by a Monoclonal Antibody to Rickettsia typhi. (September 2001) - Lee, Jae-Rin; Chang, Yoon-Young; Hahn, Myong-Joon
The epitope recognized by a mouse monoclonal antibody (MAb) to the crystalline surface layer protein of Rickettsia typhi, SRT10, was mapped to 10 amino acid residues (SRTag TFIGAIATDT). The oligonucleotide sequence covering the epitope recognized by SRT10 was inserted into a mammalian expression vector together with multiple cloning sites. When the SRTag was fused in frame to the coding region of the NCC27/CLIC1 gene and expressed in mammalian cells, the MAb SRT10 could detect the tagged protein by immunoblotting, immunocytochemistry, and immunoprecipitation. In addition to the SRT-NCC27/CLIC1, SRT10 could detect N-terminal-tagged MEF2D and C-terminal-tagged CD4 by immunocytochemistry. We suggest that this specific recognition of the SRTag by SRT10 is generally applicable to cellular and molecular biology research that requires the expression and detection of fusion proteins.